Eosinophils in health and disease: the LIAR hypothesis - J. J. Lee; Elizabeth A. Jacobsen; Michael P. McGarry; R.P. Schleimer; N. A. Lee (2010)
Summary Discussions of eosinophils are often descriptions of end‐stage effector cells with destructive capabilities mediated predominantly by released cytotoxic cationic granule proteins. Moreover, eosinophils in the medical literature are invariably associated with the pathologies linked with helminth infections or allergic diseases such as asthma. This has led to an almost fatalist view of eosinophil effector functions and associated therapeutic strategies targeting these cells that would make even William of Ockham proud – eosinophil effector functions have physiological consequences that increase patient morbidity/mortality and ‘the only good eosinophils are dead eosinophils’. Unfortunately, the strengths of dogmas are also their greatest weaknesses. Namely, while the repetitive proclamation of dogmatic concepts by authoritative sources (i.e. reviews, meeting proceedings, textbooks, etc.) builds consensus within the medical community and lower the entropies surrounding difficult issues, they often ignore not easily explained details and place diminished importance on alternative hypotheses. The goal of this perspective is twofold: (i) we will review recent observations regarding eosinophils and their activities as well as reinterpret earlier data as part of the synthesis of a new paradigm. In this paradigm, we hypothesize that eosinophils accumulate at unique sites in response to cell turnover or in response to local stem cell activity(ies). We further suggest that this accumulation is part of one or more mechanisms regulating tissue homeostasis. Specifically, instead of immune cells exclusively mediating innate host defence, we suggest that accumulating tissue eosinophils are actually regulators of L ocal I mmunity A nd/or R emodeling/ R epair in both health and disease – the LIAR hypothesis; (ii) we want to be inflammatory (pun intended!) and challenge the currently common perspective of eosinophils as destructive end‐stage effector cells. Our hope is to create more questions than we answer and provoke everyone to spend countless hours simply to prove us wrong! Cite this as : J. J. Lee, E. A. Jacobsen, M. P. McGarry, R. P. Schleimer and N. A. Lee, Clinical & Experimental Allergy , 2010 (40) 563–575